2015
DOI: 10.1109/tac.2015.2440568
|View full text |Cite
|
Sign up to set email alerts
|

Convergence Time for Unbiased Quantized Consensus Over Static and Dynamic Networks

Abstract: Abstract-In this paper, the question of expected time to convergence is addressed for unbiased quantized consensus on undirected connected graphs, and some strong results are obtained. The paper first provides a tight expression for the expected convergence time of the unbiased quantized consensus over general but fixed networks. It is shown that the maximum expected convergence time lies within a constant factor of the maximum hitting time of an appropriate lazy random walk, using the theory of harmonic funct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…In [20], some common classes of agent networks are considered while further studies on static and time-varying networks can be found in [14], [42]. It is however noted that these works deal with the problem of average consensus where the underlying graph is undirected.…”
Section: Remark 33mentioning
confidence: 99%
“…In [20], some common classes of agent networks are considered while further studies on static and time-varying networks can be found in [14], [42]. It is however noted that these works deal with the problem of average consensus where the underlying graph is undirected.…”
Section: Remark 33mentioning
confidence: 99%
“…On the other hand, as an important issue, data quantization has received extensive attention in multiagent systems. Theoretical results in the past two years include [10][11][12][13][14][15][16]. The consensus of multiagent systems is studied according to the robust learning control approach in [10].…”
Section: Introductionmentioning
confidence: 99%
“…The paper [6] obtained an upper bound of O(n 2 ), but only on complete graphs. Recently, it was shown in [8] that a certain "unbiased" quantized consensus protocol has maximum expected convergence time of O(nmD log n) on static networks where m and D denote the number of edges and the diameter of the network, and has maximum expected convergence time O(nm max D max log 2 n) on connected time-varying networks, where m max and D max denote, respectively, the maximum number of edges and the maximum diameter in the sequence of time-varying networks. Unbiasedness means that each step of the protocol was based on choosing a random edge uniformly among all possible edges in the network.…”
Section: Introductionmentioning
confidence: 99%